Successful Stem Cell Transplantation in a Patient with Pretransplant Hepatic Inflammatory Pseudotumour. (28th November 2016) - de Mel, Sanjay; Soe, Zarni; Wong, Benjamin; Ong, Ching Ching; Teo, Lynette; Tan, Lip Kun
Abstract : Inflammatory pseudotumours (IPT) are rare benign neoplasms of unknown aetiology. We present a case of hepatic IPT which was incidentally discovered in a patient with relapsed B-acute lymphoblastic leukaemia (B-ALL) undergoing pretransplant workup. After investigation to exclude an infective cause she underwent a reduced intensity conditioning stem cell transplant (SCT) successfully and currently remains well and in remission. On repeat liver MRI after SCT, the IPT was seen to be resolving. To the best of our knowledge this is the first report of an adult patient with hepatic IPT successfully undergoing SCT. The reduction in size of the IPT after SCT also suggests an inflammatory rather than an infective aetiology for IPT.